Electrowetting on dielectric driven droplet resonance and mixing enhancement in parallel-plate configuration - Lee, Chiun-Peng (American Institute of Physics, 2012)
This study experimentally verifies that the mixing process in a droplet can be enhanced by driving the droplet at resonant frequencies and at alternating driving frequencies using a parallel-plate electrowetting on dielectric device. The mixing time, which is defined as the time required for reaching the well-mixed state, in a resonant droplet is found to be significantly shorter than that in a non-resonant droplet. Besides, it is also found that a higher driving potential leads to a better mixing effect, especially at resonant frequencies. Furthermore, when a droplet is driven by alternating two driving frequencies, especially two resonant frequencies, the mixing efficiency is found to be significantly enhanced for a specific alternating duration of these two frequencies.